Music, piety and political power in 17th-century Salzburg: the sounds of good government - Hieb, Kimberly Beck (Routledge research in music, 2025)
"Music, Piety and Political Power in 17th Century Salzburg traces the role of sacred music in the service of politics at the archbishopric of Salzburg, one of many jurisdictions that made up the Holy Roman Empire in the second half of the seventeenth century. The author reveals that the use of music to present political, cultural, religious meaning was not limited to cross-confessional communities, the Imperial capital of Vienna, or other early modern metropolitan centers such as Munich and Paris. Presenting music as a powerful cultural artifact that informs our understanding of the religious and political relationships shaping the history of central Europe, this study expands our understanding of the history of music, absolutism, and Catholicism in the seventeenth century and will be of interest to scholars working in those areas"--